2017
DOI: 10.1108/tr-02-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of mega-sporting events on hotel pricing strategies: the case of the 2014 FIFA World Cup

Abstract: Purpose-This study aims to examine the impact of a mega-sporting event "2014 FIFA World Cup" on hotel pricing strategies and performance. Design/methodology/approach-The present project examines the host regions' response to the 2014 FIFA World Cup which was established by the variance in the main hotel key performance indexes: occupancy, average daily rate, revenue per available room (RevPAR) and supply. Using data gathered from STR, this research distinctly shows how the Brazilian host regions reacted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The case study based on the 2014 Shanghai stampede tragedy revealed why it happened, in what way in affected local citizens, and for how long. Compared with traditional sociological methods, the proposed approach combines the methods of social sensing, machine learning, and natural language processing and can thus facilitate efficient data acquisition and analysis [6][7][8][9][10][11][12][13][14][15][16][17]. Compared with some of the existing social network-based public opinion mining, this paper considers the dimensions of time and geo-space in observing the impact of social events in addition to sentiment analysis and opinion mining [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case study based on the 2014 Shanghai stampede tragedy revealed why it happened, in what way in affected local citizens, and for how long. Compared with traditional sociological methods, the proposed approach combines the methods of social sensing, machine learning, and natural language processing and can thus facilitate efficient data acquisition and analysis [6][7][8][9][10][11][12][13][14][15][16][17]. Compared with some of the existing social network-based public opinion mining, this paper considers the dimensions of time and geo-space in observing the impact of social events in addition to sentiment analysis and opinion mining [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Using a social conflict analysis database, Moreno and Miguel analyzed the short-term causal impact of sports events on social unrest events in Africa [9]. Using case studies, Scholtens and Peenstra [10] and Barreda et al [11] analyzed the impact of sports events on the stock market and hotel industry, respectively. Regarding political aspects, Healy et al collected original survey data during basketball championships to study the impact of irrelevant events on voters' evaluations of government performance [12].…”
Section: Traditional Research On the Impact Of Social Eventsmentioning
confidence: 99%
“…As the accommodation capacity in the host country cannot be expanded at short notice, there is temporarily excess demand for accommodation and this in turn pushes accommodation prices upwards. As a rule, the demand for accommodation during the event period is inelastic for high-priced or high-quality room prices, indicating that travellers are willing to pay the higher prices during this specific period of time (Barreda et al, 2017).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Solberg and Preuss (2007) show that revenues per guest night (deflated by the consumer price index) in the year of the Sydney Olympics increased by 11%, but the trend is reversed thereafter. Barreda et al (2017) investigate the impact of FIFA World Cup (2014) on hotel prices (revenue per available room (RevPAR) and average daily rate (ADR)) in the participating cities. The authors find that hotel prices rise during the FIFA World Cup but quickly decrease after the event, to a price level similar to that of the pre-event period.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of hotel development, studies have shown that despite long-term pre-event planning, hotel occupancies can often fall short of expected demand, in turn impacting on the MS 17 077 Event Management E-pub economic gains promoted in event rhetoric (Barreda, Zubieta, Chen, Cassilha, & Kageyama, 2017;Sun et al, 2013). In the case of the 2009 World Games hosted in Taiwan, Sun et al (2013) found a range of factors contributed to lower than expected occupancy rates, including inefficient collaboration between stakeholders, competition from hotels in regional areas, and a perception of an unfriendly local area associated with illness, climatic conditions and political controversies.…”
Section: Ms 17 077 Event Management E-pubmentioning
confidence: 99%